2013
DOI: 10.1097/rlu.0b013e31827a0037
|View full text |Cite
|
Sign up to set email alerts
|

Increased Iodine Uptake in the Nabothian Cyst

Abstract: A 31-year-old female patient with papillary thyroid cancer, status post-total thyroidectomy and radioablation with (131)I underwent posttherapy whole-body scan with SPECT, which revealed increased iodine activity in the cervix. The subsequent ultrasound examination demonstrated that the site of elevated iodine activity was caused by cervical Nabothian cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…We have previously reported a case of increased iodine uptake in cervical nabothian cysts 2. Since then, our attention has focused on 131 I-WBS after 131 I therapy in our department; this has indicated that the rate of increased focal iodine activity in the middle of the lower abdomen of patients with DTC is higher than that considered previously.…”
Section: Introductionmentioning
confidence: 86%
“…We have previously reported a case of increased iodine uptake in cervical nabothian cysts 2. Since then, our attention has focused on 131 I-WBS after 131 I therapy in our department; this has indicated that the rate of increased focal iodine activity in the middle of the lower abdomen of patients with DTC is higher than that considered previously.…”
Section: Introductionmentioning
confidence: 86%